Lacticaseibacillus rhamnosus LRa05 mediates dynamic regulation of intestinal microbiota in mice with low-dose DSS-induced chronic mild inflammation - Dong, Yao; Gai, Zhonghui; Han, Mei; Zhao, Yunjiao (Frontiers in Microbiology, 2024)
Aim: This study aimed to investigate the effects of low-dose dextran sulfate sodium (DSS) on the induction of chronic mild inflammation in mice and to evaluate the therapeutic potential of Lacticaseibacillus rhamnosus LRa05 (LRa05) to ameliorate the associated effects. The focus was on investigating changes in inflammatory, gut microbiota, serum lipopolysaccharide (LPS) and inflammatory cytokines. Methods: Mice were exposed to a low dose of DSS to induce chronic mild inflammation and LRa05 was administered as a probiotic intervention. The experiment included determination of body weight, colon length, histological examinations, and analysis of LPS and inflammatory cytokines in serum over 12 weeks. In addition, liver function, oxidative stress and intestinal microbiota were examined to understand the comprehensive effects of DSS and LRa05. Results: Low-dose DSS did not lead to significant changes in body weight, colon length or histologic signs of inflammation. However, it led to a significant increase in serum levels of LPS, tumor necrosis factor-alpha (TNFα) and interleukin-6 (IL6). Intervention with LRa05 effectively attenuated these changes, particularly by lowering LPS levels and normalizing inflammatory cytokines. In addition, LRa05 protected against DSS-induced liver function damage and attenuated oxidative stress in the liver. Analysis of the gut microbiota demonstrated dynamic regulatory effects, where LRa05 intervention led to significant shifts in microbial populations, promoting a balanced microbiota profile. These changes are indicative of dynamic regulation by LRa05 in response to chronic mild inflammation, highlighting the probiotic’s role in modulating the gut environment. Conclusion: The LRa05 intervention showed multi-layered regulation in the chronic mild inflammation model by reducing inflammatory cytokines, maintaining liver function and restoring the balance of the gut microbiota. This provides experimental support for the potential use of LRa05 in chronic inflammation-related diseases and emphasizes the importance of probiotics for overall health. The study suggests that LRa05 is a potential therapeutic agent for the treatment of chronic inflammation associated with gut dysbiosis.